Front Cover: Near‐Infrared Circularly Polarized Luminescence through Intramolecular Excimer Formation of Oligo(p‐phenyleneethynylene)‐Based Double Helicates (Chem. Eur. J. 39/2019). Issue 39 (11th June 2019) - Miki, Koji; Noda, Takeru; Gon, Masayuki; Tanaka, Kazuo; Chujo, Yoshiki; Mizuhata, Yoshiyuki; Tokitoh, Norihiro; Ohe, Kouichi
Abstract : Carbon‐based double helicates consisting of oligo( p ‐phenyleneethynylene)s and "flexible" 2, 2'‐binaphthyls or "rigid" 9, 9′‐spirobifluorenes were synthesized. The "rigid" double helicate acts as a bright macrocyclic fluorophore. The "flexible" double helicate forms a tightly interlocked intramolecular excimer under photoirradiation, emitting near‐infrared circularly polarized luminescence with high dissymmetry factor value. More information can be found in the Full Paper by K. Miki, K. Ohe, et al. on page 9211 .